IMPLEMENTATION OF THE METHOD OF TEACHING X-RAY THERAPY IN HIGHER EDUCATIONAL INSTITUTIONS - Elmurotova Dilnoza Baxtiyorovna; Fayziyeva Nodira Alisherovna; Urmanbekova Dilfuza Sanatullayevna; Bozorov Erkin Hozhievich (Web of Journals Publishing, 2024)
The paper examines the concept of the term pedagogical technology, applying the training of students in the field of biomedical engineering of radiation therapy. The scope of application and properties of long-focus and close-focus X-ray therapy is shown. Also, the classification of X-ray therapy is given.
Keywords: X-ray therapy, educational technology, long-focus, close-focus, heel spur.